Gut bacterial profiles in Parkinson's disease: A systematic review. (25th October 2022) - Li, Zhe; Liang, Hongfeng; Hu, Yingyu; Lu, Lin; Zheng, Chunye; Fan, Yuzhen; Wu, Bin; Zou, Tao; Luo, Xiaodong; Zhang, Xinchun; Zeng, Yan; Liu, Ziyan; et al.
Abstract: Introduction: Recent advances have highlighted the relationships between gut dysbiosis and Parkinson's disease (PD). Microbiota transplantation from PD patients to mice can induce increased alpha‐synuclein‐mediated motor deficits. Human studies have identified differences in the gut microbiota of PD patients compared to healthy controls. We undertook a systematic review to evaluate the available evidence for the involvement of gut bacteria in the etiology of PD. Methods: The PubMed databank, the China National Knowledge Infrastructure databank, and Wanfang Data were searched from inception until June 2021 to identify human case–control studies that investigated relationships between PD and microbiota quantified from feces. We evaluated the resulting studies focusing on bacterial taxa that were different between PD patients and healthy controls. Results: Twenty‐six studies were found in which 53 microbial families and 98 genera exhibited differences between patients with PD and healthy controls. The genera identified by more than two studies as increased in PD were Bifidobacterium, Alistipes, Christensenella, Enterococcus, Oscillospira, Bilophila, Desulfovibrio, Escherichia/Shigella, and Akkermansia, while Prevotella, Blautia, Faecalibacterium, Fusicatenibacter, and Haemophilus had three or more reports of being lower in PD patients. More than one report demonstrated that Bacteroides, Odoribacter, Parabacteroides, Butyricicoccus, Butyrivibrio, Clostridium, Coprococcus, Lachnospira, Lactobacillus, Megasphaera, Phascolarctobacterium, Roseburia, Ruminococcus, Streptococcus, and Klebsiella were altered in both directions. Conclusion: Our review shows that the involvement of the gut microbiome in the etiology of PD may involve alterations of short‐chain fatty acids (SCFAs)‐producing bacteria and an increase in putative gut pathobionts. SCFAs‐producing bacteria may vary above or below an "optimal range, " causing imbalances. Considering that Bifidobacterium, Lactobacillus, and Akkermansia are beneficial for human health, increased Bifidobacterium and Lactobacillus in the PD gut microbiome may be associated with PD medications, especially COMT inhibitors, while a high level of Akkermansia may be associated with aging. Abstract : The role of gut bacteria in association with Parkinson's disease (PD) may involve the alterations of bacteria with the capacity to produce short‐chain fatty acids (SCFAs) and an increase in putative pathobionts, which may work together to potentially impair the intestinal barrier and/or blood–brain barrier integrity, stimulating systemic and neural inflammation. SCFAs‐producing bacteria may reduce or increase outside of an "optimal range". Considering that Bifidobacterium, Lactobacillus, and Akkermansia are beneficial for human health, the increased Bifidobacterium and Lactobacillus may be associated with PD medications, especially COMT inhibitors, while a high level of Akkermansia may be associated with aging.